Perceptions on preeclampsia and eclampsia among senior, older women, in rural Southwestern Uganda - Harriet Nabulo; Gad Ruzaaza; Francis Mugabi; Francis Bajunirwe (Journal of Global Health Reports)
# Background Eclampsia is among the leading causes of maternal mortality. It is a serious hypertensive complication of pregnancy and increases the risk of cardiovascular disease in later life. Pregnancy-related hypertension complications predispose to chronic hypertension and premature heart attacks. A significant proportion of women with preeclampsia/eclampsia does not reach the formal healthcare system or arrive too late because of certain traditional or cultural beliefs about the condition. The older, senior women in the community are knowledgeable and play a significant role in decision making regarding where mothers should seek maternal health care. Therefore, the purpose of this study was to explore the perceptions of older and senior women regarding the manifestation of, risk factors and possible causes of preeclampsia/eclampsia.